Analisis Analisis Persepsi Pelaku Usaha Mikro Kecil dan Menengah tentang Proses Sertifikasi Halal Melalui BPJPH - Devi, Abrista; Mutoharoh, Arum (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia has a population with the largerst Muslim majoritym the number of Muslim residents in Indonesia is 240,62 million people as of 2023. Making Indonesia one of the Asian countries that has great potential as a producer of halal products. Apart from that, the government also requires halal sertifiction for food and beverage products starting in 2024. The halal sertification process in the new era currently involves three components that are in synergy with each other. Namely, through the Halal Product Guarantee Organizing Agency (HPGOA), The Indonesian Ulema Council (IUC) and the Halal Inspection Institution (HII). This research aims to determine the perceptions of micro, small and medium enterprises regarding the halal sertification process through HPGOA in Bogor. The Research method used in this research is a descriptive quantitative research method, in which the data research process involves distributing closed and open combination questionnaires. The research result show that business actors in Bogor have a good Perception of the halal certification process, they have high awareness as produsers, will be halal remember many consumer muslim of course, it requires official validation in the form of halal label. However, for some business actors, especially small ones, they have limitations such as costs and lack of information, so that there are still many business actors in Bogor who have not registered for halal certification. However, the government still requires a halal certification policy for business actors by providing halal supervisors and a free halal registration program through the Religious Affairs Office (RAO) as well as the cooperative service as has been implemented by Micro, Small, and Medium Enterprises (MSMEs) in Tonjong Village Bogor Regency accompanied by education and assistance.